Imaging of transfection and intracellular release of intact, non-labeled DNA using fluorescent nanodiamonds - Petrakova, V; Benson, V; Buncek, M; Fiserova, A; Ledvina, M; Stursa, J; Cigler, P; Nesladek, M (Nanoscale, 2016)
Efficient delivery of stabilized nucleic acids (NAs) into cells and release of the NA payload are crucial points in the transfection process. Here we report on the fabrication of a nanoscopic cellular delivery carrier that is additionally combined with a label-free intracellular sensor device, based on biocompatible fluorescent nanodiamond particles. The sensing function is engineered into nanodiamonds by using nitrogen-vacancy color centers, providing stable non-blinking luminescence. The device is used for monitoring NA transfection and the payload release in cells. The unpacking of NAs from a poly(ethyleneimine)-terminated nanodiamond surface is monitored using the color shift of nitrogen-vacancy centers in the diamond, which serve as a nanoscopic electric charge sensor. The proposed device innovates the strategies for NA imaging and delivery, by providing detection of the intracellular release of non-labeled NAs without affecting cellular processing of the NAs. Our system highlights the potential of nanodiamonds to act not merely as labels but also as non-toxic and non-photobleachable fluorescent biosensors reporting complex molecular events.
Keywords: Luminescence; DNA; Transfection; Nanodiamonds; transfekce; Animals; nanodiamanty; HT29 Cells; Humans; lidé; zvířata; luminiscence; Mice, Inbred DBA; buňky HT-29; myši inbrední DBA